Ion Beam Synthesis of Doped Nanocrystals of Si1-xGex Alloys Embedded in SiO2. (16th January 2017) - Chelouche, A.; Schmerber, G.; Ferblantier, G.; Muller, D.; Mathiot, D.
ABSTRACT: As an extension of our previous proving that ion beam synthesis is an efficient route to form doped silicon nanocrystals (nc's) [1, 2], we show here that ion beam synthesis, by co-implantion of the dopant and of the constituents of the alloy, followed by a single high temperature anneal, is also a convenient way to grow more complex structures, such as As doped nc's of Si1-x Gex alloys. Rutherford backscattering spectrometry (RBS) is used to measure the impurity profiles and evaluate the average concentration of the various species (Si, Ge, As). The formation of the nc's is evidenced by TEM observation and further confirmed by Raman and XRD analysis, which also allow us to estimate the Ge content of the nc's. The incorporation of As inside the Si1-x Gex nc's is attested by the presence of the characteristic Ge-As related line in the Raman spectra of the As-doped samples, and strengthened by the increased conductivity of MOS structure including such doped nc's inside the dielectric film.